Development of a manual for standardizing the teachers recruitment process - Poppy Rusdi; Bakhrani A Rauf; Thamrin Tahir (Universal Teaching and Learning Journal, 2025)
Purpose: This study aims to design clear and structured guidelines to ensure that each stage of the teacher recruitment process is conducted consistently and in accordance with established standards. Research Methodology: This study adopts a research and development (R&D) approach using the Thiagarajan et al. 4D model, which includes four stages: define, design, develop, and disseminate. Data were collected through surveys, interviews, and questionnaires, and analyzed using both qualitative and quantitative descriptive methods. Results: The teacher recruitment manual comprised objectives, procedures, and selection criteria. The development process followed the 4D stages, resulting in validation scores from HR management experts (41 points, 75%), education management experts (32.5 points, 81%), and language experts (54 points, 98%). Practicality testing with stakeholders achieved a score of 4.24 (85%), indicating that the manual is practical and ready for use. Conclusions: This study successfully produced a teacher recruitment manual that meets expert validation standards and is deemed practical by stakeholders, making it suitable for implementation in educational institutions. Limitations: This study was limited to a specific institutional context, which may affect the generalizability of the results. Broader application would require adaptation to different educational environments. Contribution: This study contributes a validated and practical recruitment manual that can serve as a model for improving recruitment consistency and quality in educational institutions.